Kerjasama Kelembagaan Antara BP2MI dan Ditjen Imigrasi dalam Pencegahan Pekerja Migran Indonesia Non Prosedural di Bandara Soekarno Hatta - Werdy Satrio Bayuaji; Puspitasari Puspitasari (Syntax Corporation Indonesia, 2024)
The non-procedural departure of Indonesian Migrant Workers (PMI) is a serious problem in Indonesia, especially due to the high risk of exploitation and human trafficking faced by migrant workers. Soekarno-Hatta International Airport as the main departure point is a strategic location in an effort to prevent non-procedural migrant workers. Cooperation between the Indonesian Migrant Workers Protection Agency (BP2MI) and the Directorate General of Immigration is crucial in ensuring that only migrant workers who meet official procedures can depart, in order to provide more effective protection. This study uses a qualitative approach with a descriptive case study method. Data are collected through the review of policy documents. The cooperation between BP2MI and Immigration has made a significant contribution in preventing thousands of non-procedural migrant workers from going abroad. However, this study also reveals the need for increased cooperation in several aspects. Policy reforms are needed, especially in immigration policies related to the supervision and control system at the point of departure, as well as policies that regulate the protection of migrant workers, both before departure and after return. With this policy reform, it is hoped that the collaboration between BP2MI and Immigration can be more effective and sustainable in protecting migrant workers from potential exploitation and human trafficking.